Increase in Oral Malodor in Patients with fixed orthodontic treatment - Shahida Maqbool, Hina Mahmood, Abdul Manan Shahid, Sobia Siddique, Farah Farhan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Oral malodor is a breath, offensive to other people. It is considered to affect huge number of the people due to certain variable causes and intensity. Malodor may indicate towards some systemic complications but 80–90% is related to intraoral conditions. Aim: To determine the mean rise in oral malodor score in patients with fixed orthodontic treatment. Methods: This Quasi experimental study was conducted at de’Montmorency College of dentistry, Lahore and consisted of six months. Non probability consecutive sampling was used to select 75 cases with 95% confidence interval. Results In this present study total 75 patient, 38(50.66%) male and 37(49.33%) female, 15 to 25 years of age were selected. Oral malodor was recorded by same doctor. The mean value of baseline malodor score (T1) was 57.57±10.32 ppb with minimum and maximum baseline oral malodor score (T1) 40 &72 ml respectively. The study results showed that the mean value of malodor score four weeks after treating the patients (T2), was 95.08 ± 8.75 ppb with minimum and maximum malodor score 81 & 110 ppb respectively. In this study, mean increase in malodor four weeks after treating patients was 37.50±14.72 ppb with minimum and maximum increase in malodor score 12 & 67 ppb respectively. Paired t-test was found significant. In our study the mean value of baseline malodor score (T1) in males (n=38) was 58.056±10.02 ppb. And in females (n=37) was 94.89±8.98 ppb. Conclusion Our study results concluded that the baseline oral malodor score was (T1) 57.57 ± 10.32 and after 4 weeks of treatment was (T2) 95.08 ± 8.75 and a mean increase on oral malodor score was 37.50 ± 14.72.